Bachelor of nursing student' attitude towards people with mental illness and career choices in psychiatric nursing. An Indian perspective - Poreddi Vijayalakshmi; Rohini Thimmaiah; Rama Chandra; Suresh BadaMath (Universidad de Antioquia, 2015)
Objective. To examine undergraduate nursing student' attitudes toward people with mental illness and mental health nursing. Methodology. This was a cross sectional descriptive study carried out among conveniently selected nursing students (N=116). Data was collected through self- reported questionnaires. Results: Majority of the participants agreed that the theoretical (81.1%) and cpnical placement (85.4%) was adequate. Similarly, 62.9% would pke to apply for a post-basic program in Psychiatric nursing and 69.8% of the students intend to pursue their career as mental health nurses. However, a majority expressed that people with mental illness are unpredictable (80.2%), cannot handle too much responsibipty (71.5%), more pkely to commit offences or crimes (84.5%) and more pkely to be violent (44%). Negative stereotype domain had significant relationships with future career (r=-0.2, p= 0.003), course effectiveness (r=-0.4, p<0.001), valuable contribution (r=-0.3, p<0.001) and readiness of the students (r=-.3, p<.000) domains. Conclusion. There is an urgent need to address these negative perceptions among nursing students towards people with mental illness. Innovative teaching strategies and appropriate changes in the nursing curriculum is required to prepare future nurses to deal mental health problems effectively.